Hepatic encephalopathy in dogs and cats. Issue 4 (8th April 2016) - Lidbury, Jonathan A.; Cook, Audrey K.; Steiner, Jörg M.
Abstract: Objective: To comparatively review the pathogenesis, clinical presentation, diagnosis, and management of hepatic encephalopathy (HE) in dogs and cats. Data Sources: The Medline database was searched for articles related to HE in people, dogs, and cats. Articles published within the last 5 years were given special importance. Human Data Synthesis: The pathogenesis of HE is complex and incompletely understood, but ammonia appears to play a central role. Hyperammonemia leads to accumulation of glutamine in astrocytes, with subsequent astrocyte swelling and neurological dysfunction. The development of HE in patients with hepatic cirrhosis is a poor prognostic indicator. The fermentable disaccharide lactulose and the antimicrobial rifaximin are US Food and Drug Administration approved treatments for human HE. Severe protein restriction is no longer recommended for patients with this condition. Veterinary Data Synthesis: HE is often associated with portosystemic shunting in dogs and cats. Ammonia plays a central role in the pathogenesis of HE in dogs and cats, but other factors such as manganese and endogenous benzodiazepines may also contribute. Recently, a soy protein‐based diet was found to be beneficial in treating canine HE. Severe dietary protein restriction is likely to be detrimental in affected animals. There have been no clinical trials of drugs routinely used in the management HE in veterinary medicine, but lactulose and antimicrobials such as metronidazole are well‐established treatments. Conclusions: HE is a potentially life‐threatening condition that is probably underdiagnosed in companion animals. Although various treatment recommendations have been proposed, there is a lack of evidence in the veterinary literature regarding optimal strategies for the management of this condition. As our understanding of the pathogenesis of HE in dogs and cats evolves, novel diagnostic tests and therapeutic agents may become available.